HUBUNGAN PENGETAHUAN PERAWAT TENTANG TIMBANG TERIMA DENGAN PELAKSANAAN TIMBANG TERIMA DALAM APLIKASI MAKP MODIFIKASI TIM PRIMER - Mono Pratiko Gustomi; Edi Mulyo Utomo (Jurnal Penelitian Multidisiplin, 2023)
Hand Over is a way of submitting and receiving reports relating to the patient's condition. At the Petrokimia Hospital of Gresik,Nurses still carry out the hand over, not in accordance with the SOP, nurses do the hand over based on medical diagnoses, collaborative and dependent interventions without explaining the nursing problems that still arise, This study aims to analyze the relationship between nurses' knowledge about the hand over and implementation of weighing in the application MAKP primary modification. The research design used was a correlation with a cross sectional approach. Statistical tests used the Spearman correlation test. The population is all nurses of 41 respondents. The measuring instrument used to find out the knowledge of nurses is the questionnaire and to find out the implementation weighs it with an checklist. The results showed that the majority of nurses who had sufficient knowledge amounted to 82.9% and most of the implementation weighed less than 78%. The test results show that the correlation coefficient of the calculation is -0.133 and significance (α) of = 0.406 means that H1 is rejected and Ho is accepted, there is no relationship between nurses' knowledge about the acceptability and implementation of the weigh in the MAKP Modification Primary Team application. The suggestion of researchers to improve the implementation of hand over is that nurses must have responsibility and good time management, the Hospital conducts,in house training, SOP socialization and accepts periodic monitoring and evaluation periodically on the implementation of hand over in the MAKP Modification Primary Team application.